Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1002/bjs.1800750306
|View full text |Cite
|
Sign up to set email alerts
|

Necrosectomy and postoperative local lavage in necrotizing pancreatitis

Abstract: Necrosectomy with postoperative continuous local lavage was performed in a prospective study involving 95 patients with necrotizing pancreatitis. In the same period 567 patients with oedematous-interstitial pancreatitis were treated non-operatively with a hospital mortality rate of 0.7 per cent. In patients with necrotizing pancreatitis the median Ranson criteria score was 4.5 points; operation was required at a median of 7 days after the onset of symptoms because of non-response to conservative treatment. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
176
1
15

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(200 citation statements)
references
References 33 publications
5
176
1
15
Order By: Relevance
“…29 Excellent results have been obtained with debridement and closed packing 22 debridement and local lavage 20,30 and debridement with open drainage. 31 A review of the literature performed by D'Egidio and Schein 32 found mortality rates of 36%, 23% and 25% respectively for the above three techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Excellent results have been obtained with debridement and closed packing 22 debridement and local lavage 20,30 and debridement with open drainage. 31 A review of the literature performed by D'Egidio and Schein 32 found mortality rates of 36%, 23% and 25% respectively for the above three techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do represent a consecutive series of patients managed in a specific and consistent way. Continuous postoperative lavage as opposed to open packing has been demonstrated to allow safe evacuation of devitalised tissues without the need for routine reoperation 30 with minimal risk of gastrointestinal fistula formation or postoperative haemorrhage. 32,37 The authors are aware of the recognised risks following splenectomy, 38,39 but feels this to be small compared with the advantages to be gained from a more complete one-off debridement set against the background of a condition with at least 20% mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is recommended for all patients with necrotising pancreatitis in whom the systemic inflammatory response syndrome persists beyond the first week after onset of symptoms. 73 Aggressive pancreatic debridement (Necrosectomy) remains the standard surgical procedure, 74,75 and may require multiple abdominal explorations. This removes the infective necrotic tissue that drives the systemic inflammatory response leading to multiple organ failure.…”
Section: Controversial Aspects Of Surgery In Necrotising Pancreatitismentioning
confidence: 99%
“…Among them, debridement with external drainage, associated with postoperative peritoneal lavage and the program scheduled for reoperation, either closing the cavity or using the laparostomy 7,9,10,11,17,33,51,52,54,57,60 .…”
Section: Collections and Pancreatic Abscessmentioning
confidence: 99%
“…Thus, methods of percutaneous drainage guided by ultrasound or by CT have been used with satisfactory resolution rates and in a few days after surgery 9,19,23,31,34,60 .…”
Section: Collections and Pancreatic Abscessmentioning
confidence: 99%